2016
DOI: 10.1038/nm.4191
|View full text |Cite|
|
Sign up to set email alerts
|

Classification and characterization of microsatellite instability across 18 cancer types

Abstract: Microsatellite instability (MSI), the spontaneous loss or gain of nucleotides from repetitive DNA tracts, is a diagnostic phenotype for gastrointestinal, endometrial, and colorectal tumors, yet the landscape of instability events across a wider variety of cancer types remains poorly understood. To explore MSI across malignancies, we examined 5,930 cancer exomes from 18 cancer types at more than 200,000 microsatellite loci and constructed a genomic classifier for MSI. We identified MSI-positive tumors in 14 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
773
2
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 814 publications
(824 citation statements)
references
References 47 publications
40
773
2
9
Order By: Relevance
“…C>T mutations represent the mutator phenotype most commonly seen in MMR-deficient tumors 8 . We also analyzed microsatellite instability (MSI) in tumors using a genomic MSI classifier 9 . ARID1A protein and mRNA levels were significantly lower in tumors with MSI than in microsatellite stable (MSS) tumors (Fig.…”
mentioning
confidence: 99%
“…C>T mutations represent the mutator phenotype most commonly seen in MMR-deficient tumors 8 . We also analyzed microsatellite instability (MSI) in tumors using a genomic MSI classifier 9 . ARID1A protein and mRNA levels were significantly lower in tumors with MSI than in microsatellite stable (MSS) tumors (Fig.…”
mentioning
confidence: 99%
“…Thus, the results showed that more than half of the in silico identified microsatellites and was able to be validated and provide enough number of markers for future genetic studies in taro. The unamplified loci in the study could be caused by exists of chimeric primers, primer location across splice sites, or sequences missing (Hause et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequences include only encoding sequences, from which a high quality of functional information can help to reveal the molecular mechanisms and genetic maps (Fu et al, 2013;Hause et al, 2016). In addition, transcriptome data is feasible for a large-scale development of microsatellite markers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the molecular diagnosis of MSI combined with immunohistochemical (IHC) analysis of MMR protein expression has been considered as a useful tool to identify patients with Lynch syndrome (LS), to improve prognostication and to guide potential tailored therapies 1 2. In contrast to colorectal cancer, where consensus guidelines for MMR-deficiency testing have been reported,3 4 the identification of MSI in gynaecological cancers (GC) still represents a challenge, especially for the ovarian tumours that remain little investigated 3–6.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to colorectal cancer, where consensus guidelines for MMR-deficiency testing have been reported,3 4 the identification of MSI in gynaecological cancers (GC) still represents a challenge, especially for the ovarian tumours that remain little investigated 3–6. This may be due to the use of a colon-specific MSI panel to extra-colorectal sites as well as to the different biology of tumours arising in different sites 2 3. In recent years, many authors have looked for new loci in noncoding or coding sequences (target genes) to identify potentially informative repeats specific for GC and to better clarify molecular steps of endometrial tumourigenesis.…”
Section: Introductionmentioning
confidence: 99%